2022
DOI: 10.1002/ecy.3896
|View full text |Cite
|
Sign up to set email alerts
|

Tree diversity effects on productivity depend on mycorrhizae and life strategies in a temperate forest experiment

Abstract: Tree species are known to predominantly interact either with arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi. However, there is a knowledge gap regarding whether these mycorrhizae differently influence biodiversity-ecosystem functioning (BEF) relationships and whether a combination of both can increase community productivity. In 2015, we established a tree-diversity experiment by growing tree communities with varying species richness levels (one, two, or four species) and either with AM or EM tree sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 69 publications
5
38
2
1
Order By: Relevance
“…Our findings that, instead, DBRs in null communities are more positive or less negative than in observed communities (Figure 5) therefore suggest strong negative effects of mycorrhizal dominance, across scales. Unlike other mycorrhiza-related BEF studies that mostly suggested a positive effect of mycorrhizal associations on BEF relationships (e.g., Dietrich et al, 2023;Ferlian et al, 2018), we presented the first multiscale evidence for the negative effect of mycorrhizal dominance on BEF relationships, which we propose as a novel mycorrhizal dominance mechanism (Figure 1). However, we acknowledge that as a new explanation for the observed scaledependent BEF relationships, this mycorrhizal dominance mechanism still needs more sequent studies to be fully tested (see following Discussion section).…”
Section: Understanding Scale-dependent Bef Patterns Via Mycorrhizal F...contrasting
confidence: 58%
See 1 more Smart Citation
“…Our findings that, instead, DBRs in null communities are more positive or less negative than in observed communities (Figure 5) therefore suggest strong negative effects of mycorrhizal dominance, across scales. Unlike other mycorrhiza-related BEF studies that mostly suggested a positive effect of mycorrhizal associations on BEF relationships (e.g., Dietrich et al, 2023;Ferlian et al, 2018), we presented the first multiscale evidence for the negative effect of mycorrhizal dominance on BEF relationships, which we propose as a novel mycorrhizal dominance mechanism (Figure 1). However, we acknowledge that as a new explanation for the observed scaledependent BEF relationships, this mycorrhizal dominance mechanism still needs more sequent studies to be fully tested (see following Discussion section).…”
Section: Understanding Scale-dependent Bef Patterns Via Mycorrhizal F...contrasting
confidence: 58%
“…Although recent biodiversity experiments suggested that mycorrhizal functions can drive the positive BEF patterns in different ecosystems (Deng et al, 2023;Dietrich et al, 2023;Ferlian et al, 2018;Luo et al, 2017;Schnitzer et al, 2011), these findings were obtained under highly controlled environmental conditions and might not be informative for BEF observations in field studies (Hagan et al, 2021). Given the scale-dependent property of BEF patterns in natural forests (Chisholm et al, 2013), the fact that most mycorrhiza-related BEF studies have been conducted at one individual scale (actually often at scales smaller than 0.1 ha) limits the practical value of mycorrhizal functions for managing "real-world" forests (Manning et al, 2019).…”
Section: Understanding Scale-dependent Bef Patterns Via Mycorrhizal F...mentioning
confidence: 99%
“…Besides effects on the life strategies of the host, the two types of mycorrhizal fungi largely shape the soil microbial communities (Heděnec et al, 2020;Singavarapu et al, 2022) as well as higher trophic groups in the soil food web (Peng et al, 2022). Taken together, mycorrhizal types are likely to co-determine forest BEF relationships, as indicated by recent work (Deng et al, 2023;Dietrich et al, 2023;Luo et al, 2023;Yan et al, 2022). Due to the cascading effects across trophic levels (Eisenhauer et al, 2013;Schuldt et al, 2018), mycorrhizal association types can potentially shape the relationship between tree diversity and multitrophic ecosystem functions; however, empirical evidence is lacking thus far.…”
Section: Introductionmentioning
confidence: 93%
“…While EM tree species generally benefit from greater nitrogen mobilization from organic matter and enhanced organic and inorganic resource uptake (32), trees associated with AM fungi mainly benefit from greater uptake of less mobile nutrients such as phosphorus (26)(27)(28)(29). Mycorrhizal associations with AM or EM fungi are known to influence tree productivity differently (33)(34)(35). For instance, Deng et al (36) found that differences in nutrient acquisition strategies affect the direction of BPRs, with positive effects of tree species richness on AM tree productivity but negative effects for EM trees.…”
Section: Introductionmentioning
confidence: 99%